2013
DOI: 10.1002/micr.22137
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of contralateral C7 transfer to two recipient nerves in 22 patients with the total brachial plexus avulsion injury

Abstract: The treatment of total brachial plexus avulsion injury is difficult with unfavorable prognosis. This report presents our experience on the contralateral C7 (CC7) nerve root transfer to neurotize two recipient nerves in the patients with total BPAI. Twenty-two patients underwent CC7 transfer to two target nerves in the injured upper limb. The patients' ages ranged from 13 to 48 years. The entire CC7 was transferred to pedicled ulnar nerve in the first stage. The interval between trauma and surgery ranged from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…37 On the other hand, elbow and wrist extension functions are not as critical for the patients with total brachial plexus injury; therefore, only a few reports of CC7 transfer to radial or triceps nerve, which contained a small number of patients. 7, 1719, 38, 43, 49 In our study, 66% of the included patients had total brachial plexus avulsion injuries; spontaneous recovery innervated with the other root is very unlikely. The short distance between CC7 and biceps and triceps muscles could possibly contribute to these enhanced recoveries.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…37 On the other hand, elbow and wrist extension functions are not as critical for the patients with total brachial plexus injury; therefore, only a few reports of CC7 transfer to radial or triceps nerve, which contained a small number of patients. 7, 1719, 38, 43, 49 In our study, 66% of the included patients had total brachial plexus avulsion injuries; spontaneous recovery innervated with the other root is very unlikely. The short distance between CC7 and biceps and triceps muscles could possibly contribute to these enhanced recoveries.…”
Section: Discussionmentioning
confidence: 55%
“…Fourteen studies reported outcomes of multiple procedures. 7, 10, 1719, 28, 30, 31, 37, 38, 40, 43, 46, 49 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have described limited results using grafts, supraclavicular nerve, intercostal nerves or contralateral C7 as donors [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] . Detailed data are shown in Table 2.…”
Section: Discussionmentioning
confidence: 99%